2016
DOI: 10.1056/nejmoa1504370
|View full text |Cite
|
Sign up to set email alerts
|

Two Phase 3 Trials of Adalimumab for Hidradenitis Suppurativa

Abstract: Treatment with adalimumab (40 mg weekly), as compared with placebo, resulted in significantly higher clinical response rates in both trials at 12 weeks; rates of serious adverse events were similar in the study groups. (Funded by AbbVie; ClinicalTrials.gov numbers, NCT01468207 and NCT01468233 for PIONEER I and PIONEER II, respectively.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
654
9
31

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 592 publications
(713 citation statements)
references
References 25 publications
19
654
9
31
Order By: Relevance
“…Administration of adalimumab with a cumulative response rate of 58% (improvement ≥50% in 23 patients) has been reported in case reports with 42 patients with moderate-to-severe HS [19,100,101,102,103]. Adalimumab efficacy in HS is also supported by prospective open studies [19,104] and prospective, randomized, double-blind, placebo-controlled surveys [17,105] involving over 800 HS patients, the vast majority of whom were included in 2 phase III studies [106]. Moreover, the European Medicine Agency has recently accepted HS as an indication for adalimumab.…”
Section: Treatmentmentioning
confidence: 94%
“…Administration of adalimumab with a cumulative response rate of 58% (improvement ≥50% in 23 patients) has been reported in case reports with 42 patients with moderate-to-severe HS [19,100,101,102,103]. Adalimumab efficacy in HS is also supported by prospective open studies [19,104] and prospective, randomized, double-blind, placebo-controlled surveys [17,105] involving over 800 HS patients, the vast majority of whom were included in 2 phase III studies [106]. Moreover, the European Medicine Agency has recently accepted HS as an indication for adalimumab.…”
Section: Treatmentmentioning
confidence: 94%
“…While clinical trials have demonstrated the efficacy of adalimumab in reducing disease burden, they did not sufficiently examine the clinical response in patients with SOC (Table 1) [33-36]. One study was conducted solely in Caucasian and Romany individuals, while another consisted of 80–88% Caucasians [33, 35]. A Danish trial did not report race for any participants [36].…”
Section: Treatment Response In Socmentioning
confidence: 99%
“…1 Two phase III multicenter trials of adalimumab were recently completed, PIONEER I and II, enrolling 633 patients. 97 Clinical response rates at week 12 were significantly higher for the groups receiving adalimumab 40 mg weekly than for the placebo groups: 41.8% versus 26.0% in PIONEER I and 58.9% versus 27.6% in PIO-NEER II. 97 The differences between the two trials could be related to the fact that in PIONEER I, patients receiving oral antibiotics had to stop treatment for at least 28 days before baseline whereas in PIONEER II they were allowed to continue treatment with antibiotics (tetracycline class) in stable doses.…”
Section: -Biologic Agentsmentioning
confidence: 89%
“…97 Clinical response rates at week 12 were significantly higher for the groups receiving adalimumab 40 mg weekly than for the placebo groups: 41.8% versus 26.0% in PIONEER I and 58.9% versus 27.6% in PIO-NEER II. 97 The differences between the two trials could be related to the fact that in PIONEER I, patients receiving oral antibiotics had to stop treatment for at least 28 days before baseline whereas in PIONEER II they were allowed to continue treatment with antibiotics (tetracycline class) in stable doses. Adalimumab 160 mg week 0, 80 mg week 2, then 40 mg weekly since week 4 is currently approved for the treatment of moderate to severe HS.…”
Section: -Biologic Agentsmentioning
confidence: 89%